Catalyst-free synthesis of 3-alkenyloxindoles from isatin-derived Morita–Baylis–Hillman carbonates. (March 2017) - Jiang, Lin; Li, Yong-Gen; Li, Hang; Yuan, Ming-Wei; Chuan, Yong-Ming; Li, Hong-Li; Yuan, Ming-Long
A variety of biologically and synthetically useful 3-alkenyloxindoles were rapidly synthesised via an SN 2′-type allylic substitution reaction of isatin-derived Morita–Baylis–Hillman carbonates with sodium sulfinates. The syntheses were conducted under catalyst-free reaction conditions and good to excellent product yields (up to 96%) and Z/E selectivities (up to >20:1) were obtained.